2006
DOI: 10.1124/dmd.106.012104
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Metabolism of l-Methionine in Mice: Evidence for Stereoselective Formation of Methionine-d-Sulfoxide and Quantitation of Other Major Metabolites

Abstract: Flavin-containing monooxygenases (FMOs) are microsomal enzymes that catalyze the NADPH-and O 2 -dependent oxidation of heteroatoms (nitrogen, sulfur, phosphorus) present in the chemical structure of a variety of drugs and xenobiotics. Five functional forms (FMO1-5) have been characterized to date (Ziegler, 2002). In humans, FMO1 is the primary isoform expressed in neonate liver, but a switch occurs shortly after birth to FMO3, the primary isoform expressed in adult human liver (Koukouritaki et al., 2002). In m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…Gender differences in Met metabolism such as increased Met TM and/or decreased Met TA in females could also contribute to the observed toxicological differences. In support of this hypothesis, Met-dosed female mice had higher levels of SAM present in the liver after 15 min compared with Met-dosed males (Dever and Elfarra, 2006). Further investigations are required to examine potential gender differences in 3-MTP metabolism and rates of Met TM and Met TA in mouse hepatocytes.…”
mentioning
confidence: 61%
“…Gender differences in Met metabolism such as increased Met TM and/or decreased Met TA in females could also contribute to the observed toxicological differences. In support of this hypothesis, Met-dosed female mice had higher levels of SAM present in the liver after 15 min compared with Met-dosed males (Dever and Elfarra, 2006). Further investigations are required to examine potential gender differences in 3-MTP metabolism and rates of Met TM and Met TA in mouse hepatocytes.…”
mentioning
confidence: 61%
“…From what we currently know, there is no evidence for preferential formation of one diastereomer of Met sulfoxide over the other in proteins and free amino acid forms, with the exception of enzymatic oxidation by flavin-containing monooxygenase 3 (26, 27). Prior to the discovery of Met- R -SO specific reductase, researchers focused on characterizing stereospecific oxidation by ROS because it was known that oxidized Met residues could be completely reduced in vivo , whereas only a Met- S -SO specific reductase was known at the time.…”
Section: Methionine Oxidation By Rosmentioning
confidence: 98%
“…the nonproductive decay of the hydroperoxideintermediate 59,6568 (Figure 2, step e). While mammalian FMOs have been extensively characterized as detoxifying enzymes, it has been shown that FMO1, FMO2, and FMO3 possess catalytic activity toward methionine, generating MetO 56,6972 . Interestingly, the MetO formed in liver, kidney, and lung microsomal fraction shows enrichment for the R isomer, pointing to a catalytic mechanism rather than a direct reaction with H 2 O 2 .…”
Section: Flavin-dependent Monooxygenases and Methionine Oxidationmentioning
confidence: 99%